YAP-mediated mechanotransduction in urinary bladder remodeling: Based on RNA-seq and CUT&Tag - Di, Xingpeng; Xiang, Liyuan; Jian, Zhongyu (Frontiers in Genetics, 2023)
Yes-associated protein (YAP) is an important transcriptional coactivator binding to transcriptional factors that engage in many downstream gene transcription. Partial bladder outlet obstruction (pBOO) causes a massive burden to patients and finally leads to bladder fibrosis. Several cell types engage in the pBOO pathological process, including urothelial cells, smooth muscle cells, and fibroblasts. To clarify the function of YAP in bladder fibrosis, we performed the RNA-seq and CUT&Tag of the bladder smooth muscle cell to analyze the YAP ablation of human bladder smooth muscle cells (hBdSMCs) and immunoprecipitation of YAP. 141 differentially expressed genes (DEGs) were identified through RNA-seq between YAP-knockdown and nature control. After matching with the results of CUT&Tag, 36 genes were regulated directly by YAP. Then we sheltered the hub genes in the DEGs, including CDCA5, CENPA, DTL, NCAPH, and NEIL3, that contribute to cell proliferation. Thus, our study provides a regulatory network of YAP in smooth muscle proliferation. The possible effects of YAP on hBdSMC might be a vital target for pBOO-associated bladder fibrosis.